Shrinkage and tensile properties of ultra-high-performance engineered cementitious composites (UHP-ECC) containing superabsorbent polymers (SAP) and united expansion agent (UEA). (11th July 2022) - Wu, Li-Shan; Yu, Zhi-Hui; Zhang, Cong; Yuan, Zhen; Bangi, Toshiyuki
Highlights: The incorporation of superabsorbent polymer (SAP) and united expansion agent (UEA) could effectively mitigate the autogenous shrinkage. The inclusion of SAP reduced the fracture toughness by increasing the matrix porosity, thus improving the multiple cracking and strain-hardening behavior of UHP-ECC. Pseudo strain hardening index of each specimen was conducted to explain the effect of incorporation of SAP and UEA on the tensile properties of UHP-ECC. Abstract: Ultra-high performance engineered cementitious composites (UHP-ECC) had received extensive attention in recent years in material as well as the field of structural rehabilitation and strengthening due to its excellent mechanical properties, such as high strength and high ductility. However, the high shrinkage is one of the bottlenecks limiting widespread engineering application of UHP-ECC. In this paper, superabsorbent polymers (SAP) and United expansion agent (UEA) were introduced to mitigate UHP-ECC shrinkage. And the effect of different amounts of SAP with UEA on the shrinkage and tensile properties of UHP-ECC are investigate. Results indicate that the incorporation of SAP and UEA can effectively mitigate the autogenous shrinkage, and the autogenous shrinkage decreased with the increasing SAP dosage; however, drying shrinkage had the opposite trend. The incorporation of SAP and UEA improved the tensile ductility of UHP-ECC. The inclusion of SAP reduced the fracture toughness by increasing the matrix porosity, which produced more micro-cracking sources, thus improving the multiple cracking and strain-hardening behaviors of UHP-ECC. Conversely, the incorporation of SAP decreased the fiber/matrix interaction as well as decreasing the effective number of polyethylene (PE) fibers in the cross-section, thus reducing the tensile strength. Finally, pseudo strain hardening index of each specimen was conducted to analyze the effect of SAP with UEA on the tensile properties of UHP-ECC.